Decreased Severity in Recurrent Versus Initial Episodes of Acute Pancreatitis. Issue 6 (August 2015) - Lee, Peter J.W.; Bhatt, Amit; Holmes, Jordan; Podugu, Amareshwar; Lopez, Rocio; Walsh, Matthew; Stevens, Tyler
<x xml:space="preserve">Abstract</x> Objectives The comparative outcomes of initial versus recurrent acute pancreatitis (AP) have not been clearly established. Aim The aim was to compare the clinical outcomes of those with an initial episode of AP to those with recurrent AP stratified by the number of prior episodes. Methods This retrospective cohort study included consecutive patients with AP admitted to the Cleveland Clinic between 2008 and 2011. The odds of severe AP, multisystem organ failure, ICU admission, new local complications, elevated blood urea nitrogen and bedside index for severity in acute pancreatitis score, systemic inflammatory response syndrome, and mortality were compared using univariable and multivariable logistic regression. Results Two hundred and ninety two patients were included, of which 213 (72%) were admitted on their initial AP episode. Mortality in patients experiencing first episode was 4.7%, compared to 0% in patients with recurrent attack of pancreatitis (P = 0.047). Prior episodes of AP were found to be protective against multisystem organ failure (odds ratio, 0.14 for each prior episode; confidence interval, 0.01–0.76) and intensive care unit admission (0.24, confidence interval, 0.06–0.91), adjusting for potential confounding factors such as transfer status and obesity. Conclusions Patients presenting with recurrent AP may be at decreased risk of a clinically severe course and incur decreased mortality.